2018
DOI: 10.1111/jopr.12777
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Fracture Resistance of Adhesively Restored Molar Teeth with Different MOD Cavity Dimensions

Abstract: Within the limitations of this investigation, the following conclusions can be drawn regarding molar teeth with a MOD cavity: 3 mm or shallower cavities can be restored to the physiological fracture strength with direct composite restorations; 5 mm or deeper cavities cannot be restored to the physiological fracture strength with direct composite restorations. Cusp thickness does not significantly influence fracture strength in molar MOD cavities with a direct composite restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
37
1
6

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 43 publications
5
37
1
6
Order By: Relevance
“…In our study, teeth restored with layered composite fillings ( ) showed significantly lower fracture resistance than intact teeth (group 12) (p = 0.033). This is in accordance with the results of Förster et al, showing that molar not root canal treated teeth with deep cavities cannot be successfully reinforced with direct composite fillings ( Forster et al, 2019 ). The same was shown by Papadopoulos et al, when they compared the fracture resistance of natural teeth with MOD cavities restored with a bulk-fill composite ( Papadopoulos et al, 2018 ).…”
Section: Groupsupporting
confidence: 91%
“…In our study, teeth restored with layered composite fillings ( ) showed significantly lower fracture resistance than intact teeth (group 12) (p = 0.033). This is in accordance with the results of Förster et al, showing that molar not root canal treated teeth with deep cavities cannot be successfully reinforced with direct composite fillings ( Forster et al, 2019 ). The same was shown by Papadopoulos et al, when they compared the fracture resistance of natural teeth with MOD cavities restored with a bulk-fill composite ( Papadopoulos et al, 2018 ).…”
Section: Groupsupporting
confidence: 91%
“…In vitro biomechanikai témájú vizsgálatok azt találták, hogy az amalgám nem nyújt elegendő megerősítést egy MOD kavitás esetében [33,19], és sokszor a megmaradt falak megrepedéséhez és töréséhez vezethet. Ugyanakkor Forster és munkatársai in vitro vizsgálatukban azt találták, hogy mélyebb MOD ka-vitások esetén a hagyományos kompozit tömés sem képes megerősíteni a fogat és visszaadni az egészséges foggal azonos töréssel szembeni ellenállás értéket [8]. Ennek a hátterében számos tényező áll, ezek egy része az alkalmazott restauratív anyagra (polimerizációs zsugorodás, töréssel szembeni szívósság), egy része pedig az operátorra (izolálás, alkalmazott ragasztási és applikációs technika stb.)…”
Section: Bevezetésunclassified
“…osztályú MOD kavitásokat 2,5 mm-es falvastagsággal és 5 mm-es mélységgel (csücsökcsúcshoz képest), amelyet egy korona-falvastagságmérő és egy hagyományos parodontológiai szonda (Hu-Friedy Mfg. Co., Chicago, USA) segítségével kontrolláltunk [8]. A kavitás mélységét mindig a kavitás adott részéhez tartozó csücsök csúcsától mértük úgy, hogy a paro don to ló giai szonda érintkezzen az axiális fallal.…”
Section: Vizsgálati Anyag éS Módszerunclassified
See 1 more Smart Citation
“…In case of anterior teeth the loading tip is positioned at a 30-45 degrees to the long axis of the tooth in order to simulate the normal relationship of the front teeth. The bar delivering the loading is usually a rounded, 6 mm diameter stainless-steel ball-shaped stylus [12]. Some research groups were trying to incorporate a more realistic relationship and contact with the opposing dentition into their mechanical studies.…”
Section: Introductionmentioning
confidence: 99%